Latent structure of standard indicators of competitive efficiency of teams on the world basketball championship of players up to 20 years - Bajgoric, B.; Causevic, D.; Basinac, I.; Korjenic, A. (Sport Science - International Scientific Journal of Kinesiology, 2015)
The aim of this paper is defining the latent space of standard indicators of competitive effectivity in order to get the exact indicators which have great influence on the world championship success of the basketball teams up to 20 years. This research is conducted using data collected from 48 games of eight best qualified basketball teams on the U-19 world basketball championship in Serbia. The latent structure of basketball game is examined using factor analysis based on standard indicators of competitive efficiency of the game with the goal of determining their funcional dependance and to obtain complete vision of their interaction. Characteristic roots which explained 69,42% of mutual variance are obtained. The isolated factors are defined as: factor of situational precision in attack, factor of situational lucidity of players in defence as well in the offense, factor of situational unprecision and anticipation of shoot in offense, factor of situational efficiency in jumps and in free throws, and the last, factor of situational aggressivity and precision of shoot for three points